PP.30.02: RELATIONSHIP BETWEEN TRADITIONAL CARDIOVASCULAR RISK FACTORS AND MICROALBUMINURIA IN HUMAN IMMUNODEFICIENCY VIRUS-INFECTED PATIENTS. (June 2015) - Betancourt, A.; Richarz, N.; Leon, E.; Pons, N.; Garcia, I.; Cortes-Lletget, M.C.; Ruigomez, J.; Marquez, M.; Jerico, C.; Armario, P.
Abstract : Objective: To assess the prevalence of microalbuminuria and its relationship with other cardiovascular risk factors in infected subjects HIV-1(+) controlled in our institution. Design and method: Cross-sectional study. Hypertension was defined as a blood pressure greater or equal than 140/90 mmHg or being on antihypertensive treatment, diabetes mellitus (DM) as a fasting glycaemia greater or equal 126 mg/dL or antidiabetic treatment, and hypercholesterolemia as a fasting LDL cholesterol (LDLc) greater or equal than 130 mg/mL or being on treatment. Microalbuminuria was defined as an increase urinary excretion of albumin: urine albumin-to-creatinine ratio (UACR) more or equal than 30 mg/g in a spot urine (average of 2 determinations). High-normal albuminuria was defined as a UACR between 10–29 mg/g. Results: Three hundred and fifty-nine subjects are usually controlled in our unit. Two hundred and thirty three of them with UACR determinations, aged 44.7 ± 8.6 years old, 71.2% (166/233) males, were included. The prevalence of hypertension, DM, hypercholesterolemia and current smoking were 26.2% (61/233), 7.7% (18/233), 33.0% (77/233) and 45.7% (106/233) respectively. The prevalence of microalbuminuria was 5.6% (13/233). In the univariate analysis the factors associated with microalbuminuria were age higher than 50 years old (1.7% vs 17.2% p < 0.001), hypertension (2.9% vs 13.1 p < 0.005), DM (3.7% vs 27.7% p < 0.001) and hypercholesterolemia (3.2% vs 10.4% p < 0.05), but not smoking and others HIV specific factors (combination antiretroviral therapy, current HIV-1 RNA, current CD4(+) cells count, duration of HIV infection and risk behaviour of HIV aquisition). The prevalence of high-normal albuminuria was also significantly higher in subjects with hypertension, DM or hypercholesterolemia. After adjusting by age, the differences were still significant. When an analysis were performed as a continuous variable, there were a positive correlation between urinary albumin excretion and systolic blood pressure (BP) (r 2 = 0.13 p < 0.001) as well as diastolic BP (r 2 = 0.07 p < 0.001) and a weak negative correlation with nadir CD4(+) count (r 2 = 0.02 p < 0.05). Figure. No caption available. Conclusions: Hypertension, DM and hypercholesterolemia were associated with microalbuminuria and high-normal albuminuria in HIV-1(+) patients. A positive correlation was observed among albumin urinary excretion and systolic and diastolic blood pressure in these subjects.